2021
DOI: 10.3390/en15010146
|View full text |Cite
|
Sign up to set email alerts
|

Space Redevelopment of Old Landfill Located in the Zone between Urban and Protected Areas: Case Study

Abstract: Landfills are elements of the waste management system, without possibility of further reclaiming, according to the requirements of a closed-loop economy, but with the possibility of transforming the area into other functions. The research combined monitoring of plant species, suggesting the composition of vegetation cover for pro-ecological management, analysis of functional and infrastructural incorporation of the landfill in the surrounding landscape, and proposals for reclamation and social application. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Since then, cyclic geodetic monitoring on installed benchmarks has made it possible to assess the condition of the structure’s geometry in terms of horizontal displacements and subsidence. This process was aimed at preparing the landfill, which was closed in 2017, for its transformation into a public facility, i.e., a ski run for skiers, snowboarders, and tobogganers, as well as runners and cyclists [ 7 , 32 ]. The regulation [ 6 ] allows building constructions on the crown of a landfill after fifty years from the date of its closure.…”
Section: Study Areamentioning
confidence: 99%
“…Since then, cyclic geodetic monitoring on installed benchmarks has made it possible to assess the condition of the structure’s geometry in terms of horizontal displacements and subsidence. This process was aimed at preparing the landfill, which was closed in 2017, for its transformation into a public facility, i.e., a ski run for skiers, snowboarders, and tobogganers, as well as runners and cyclists [ 7 , 32 ]. The regulation [ 6 ] allows building constructions on the crown of a landfill after fifty years from the date of its closure.…”
Section: Study Areamentioning
confidence: 99%
“…Photos of waste landfills: (a) securing the slope of the landfill basin (Vaverkova, 2021); (b) mixed municipal solid waste at a landfill site containing predominantly synthetic materials (Vaverkova, 2017); (c) use of geotextiles for landfill cover (Vaverkova, 2022); (d) example of a reclaimed landfill (Koda, 2022). …”
Section: Waste Landfill Issuesmentioning
confidence: 99%
“…Artificially developed grounds composed largely of anthropogenic materials include for example closed-down historical landfills confirming the artificial/anthropogenic form: Fresh Kills Landfill and Puente Hills Landfill (New York, USA), considered as the largest man-made structure in the world (Eklund et al, 1998; Melosi, 2016); Puente Hills Landfill (Los Angeles, USA), at present, the largest biogas plant in the world (Themelis and Ulloa, 2007); Teufelsberg and Drachenberg (Berlin, Germany), landfill of war-time wastes (Edgeworth et al, 2015; Thestorf and Makki, 2022); Jardim Gramacho landfill (Rio de Janeiro, Brazil) which was inappropriately located from the geotechnical point of view (da Costa et al, 2018; Tirado-Soto and Zamberlan, 2013); Żelazny Most copper tailings disposal pond (1394 ha, Poland) (Jamiolkowski, 2014), Radiowo landfill (Warsaw, Poland) (Figure 1d), located in the buffer zone between urban development and protected areas, which encompass two natural reserves and the Kampinoski National Park (Koda and Osinski, 2017; Koda et al, 2022).…”
Section: Geological Impact Of Landfillsmentioning
confidence: 99%
“…However, blind decisions in terms of UMICU are not only detrimental to the proper allocation of spatial resources but also cause large economic losses and risks [15], [16]. Therefore, it is imperative to explore how to effectively and reasonably reuse the land resources of UMI to eliminate NIMBY effects and achieve high-quality development in high-density cities [17], [18].…”
mentioning
confidence: 99%
“…Sun et al (2019) [15] reviewed the modes, designs and cases of low-cost underground wastewater treatment plants and concluded that they become environmentally friendly, resource-intensive and sustainable wastewater treatment plants by constructing comprehensive office buildings, parking lots, sports fields and other functional buildings or green spaces in the aboveground space, alleviating the problems of urban land occupation and environmental pollution. Koda et al (2022) [18] analyzed the functional and infrastructural incorporation of the Radiowo landfill in the surrounding landscape and proposed reclamation and social applications to reintroduce it into social life. The "Guangzhou guidelines for compound land use of municipal infrastructure" issued by the Guangzhou Municipal Planning and Natural Resources Bureau (2022) [10] proposed 48 combination modes for UMICU by considering relevant excellent cases at home and abroad, such as sewage treatment plant + ground park, substation + commercial facilities, waste transfer stations + park, etc.…”
mentioning
confidence: 99%